Tradisi Semaan Al-Quran di Pondok Pesantren - Maskur Maskur (Al-Liqo: Jurnal Pendidikan Islam, 2021)
One of the efforts to study the contents of the Qur'an is Semaan tradition. This study used a qualitative approach, the subjects were Kyai, the teachers, the administrators, and the students of the Ibrohimiyyah Mranggen Islamic boarding school. The school has a lot of students ranging in age 6 to 12 years. Primary data sources were obtained directly from the field through observation and interviews, while the secondary sources were obtained from the documents. The results showed that the Semaan activities were carried out under planning, implementation, and evaluation. That was always conducted in teaching the Al-Quran to students.